Practical mathematics - Sullivan, Thomas, active 1796-1797.
Volumes IV and V only, bound as one, of a treatise on trigonometry and other mathematical topics.
Mathematician.
Collection material in English.
Keywords: Mathematics; Trigonometry; Mathematicians